2020
DOI: 10.3390/app10113761
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate-Based Lanthanum Strontium Cobalt Ferrite (LSCF)–Samarium-Doped Ceria (SDC) Composite Cathode for Low-Temperature Solid Oxide Fuel Cells

Abstract: Perovskite-based composite cathodes, La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF)–Ce0.8Sm0.2O1.9-carbonate (SDCC), were investigated as cathode materials for low-temperature solid-oxide fuel cells. The LSCF was mixed with the SDC–carbonate (SDCC) composite electrolyte at different weight percentages (i.e., 30, 40, and 50 wt %) to prepare the LSCF–SDCC composite cathode. The effect of SDCC composite electrolyte content on the diffraction pattern, microstructure, specific surface area, and electrochemical performances of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…La 0.6 Sr 0.4 Fe 0.8 Co 0.2 O 3−δ (LSFC) is the most often used in SOFCs with doped CeO 2 electrolyte membranes due to its high conductivity and excellent electro-catalytic activity to ORR in the IT-range [52,53]. It is generally accepted that the electrochemical performance of LSFC can be further improved by mixing the cathode material with an electrolyte [35,54,55]. Recently, Pikalova et al reported on the possibility of the additional activation of the composite electrodes using CuO and Bi 2 O 3 -Er(Y) 2 O 3 additives [32,56].…”
Section: Synthesis Of the Electrode Powdersmentioning
confidence: 99%
“…La 0.6 Sr 0.4 Fe 0.8 Co 0.2 O 3−δ (LSFC) is the most often used in SOFCs with doped CeO 2 electrolyte membranes due to its high conductivity and excellent electro-catalytic activity to ORR in the IT-range [52,53]. It is generally accepted that the electrochemical performance of LSFC can be further improved by mixing the cathode material with an electrolyte [35,54,55]. Recently, Pikalova et al reported on the possibility of the additional activation of the composite electrodes using CuO and Bi 2 O 3 -Er(Y) 2 O 3 additives [32,56].…”
Section: Synthesis Of the Electrode Powdersmentioning
confidence: 99%